The Prevalence of Use of FOAMED Sources Among Saudi Emergency Medicine Residents: A Cross Sectional Study - Alaska, Yasser; Aloqayli, Ahmed; Almogheer, Rakan; Aljerian, Nawfal; Arafat, Mohammed; Aldhubib, Abdulrahman; Almohaimeed, Ibrahim; Alsultan, Ali; Alhosaini, Abdulaziz; AlRabiah, Bader; et al. (International Journal of Innovative Research in Medical Science, 2022)
Introduction: New technologies in the field of learning and teaching the various scopes of medicine are being embraced now more than ever by learners and students, understanding the changes, the requirements, and the need for such tools is essential in the process of providing the proper materials most efficiently. Understanding the shift from traditional use of resources to the use of FOAMED among Saudi emergency medicine residents is important in the implementation and improvement of contemporary FOAMED tools in Saudi Arabia. In this study we aim to investigate the phenomenon called FOAMED to improve its implementation and widen its scope. Although this is becoming popular, published articles investigating its driving factors among learners have been limited. Methodology: A cross sectional study among emergency medicine residents in Riyadh, Saudi Arabia; targeting 322 EM (emergency medicine) residents with a sample size of 175. An online questionnaire, previously validated and used by Jeff Riddell et. al (7), was sent to all the residents in all levels through email and WhatsApp groups from January 2020 to September 2020. Data were analyzed using the latest version of SPSS. The Research Ethics Committee at King Saud University Hospital approved the study (IRB No. E-20-5596). Results: Of the 322 EM residents in Riyadh, Saudi Arabia, 201 residents responded and completed the questionnaire with a response rate of 62.4% (201 out of 322). The two most commonly used podcasts are EMCrack with 18.1% (94/201) and EM: RAP with 11.7% (61/201) respectively. Nearly a third 29.4% (59/201) of the total number of respondents said that they do not listen to podcasts followed by 23.9% (48/201) who listen to podcasts once a month. For the ideal length of time for an emergency medicine podcast, 30.8% (n=62/201) answered 11-20 minutes, followed by 28.9% (n=58/201) who answered 21-30 minutes. The top two reasons why residents stopped listening were “It was too long” (35.7%, n = 105/201) as well as “It was too boring;” (27.6%, n = 81/356). Highest number of residents reported that their motivation to listen to EM podcasts is “Board Review” with 21.5% (n=87/201). Conclusion: The results of our study suggested that most residents preferred to listen to podcasts of less than 30 minutes in length, which was consistent with previous studies. The main motivation for listening to podcasts among EM residents was for “Board Review”, which emphasizes the need to keep up with the newer and contemporary ways of learning among FOAMED creators in Saudi Arabia.